2013
DOI: 10.1080/01635581.2013.748924
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant RichMorus albaleaf Extract Induces Apoptosis in Human Colon and Breast Cancer Cells by the Downregulation of Nitric Oxide Produced by Inducible Nitric Oxide Synthase

Abstract: Morus species had been used widely in the traditional medicines for various diseases. In this study we report the in vitro antiproliferative activity of the methanol extract of Morus alba. The extract is capable of inducing cytotoxicity in human colon cancer (HCT-15) cells (IC(50) = 13.8 μg/ml) and breast cancer (MCF-7) cells (IC(50) = 9.2 μg/ml), resulted in significant morphological changes of the cells, fragmentation of DNA, and caspase-3 activation- characteristics of apoptosis. It downregulated the amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 16 publications
0
36
0
Order By: Relevance
“…Caspase-3 was widely used to evaluate apoptosis in MCF-7 breast cells and has been recognized as having important implications in studying phytoestrogen-mediated anti-tumor activities (24)(25)(26). Therefore, to verify whether in the presence of E 2 , these phytoestrogens can be recognized as inhibitors of apoptosis, we further investigated the mitochondrial/caspase pathway.…”
Section: Discussionmentioning
confidence: 98%
“…Caspase-3 was widely used to evaluate apoptosis in MCF-7 breast cells and has been recognized as having important implications in studying phytoestrogen-mediated anti-tumor activities (24)(25)(26). Therefore, to verify whether in the presence of E 2 , these phytoestrogens can be recognized as inhibitors of apoptosis, we further investigated the mitochondrial/caspase pathway.…”
Section: Discussionmentioning
confidence: 98%
“…Its dried leaves, called mulberry leaf in China, have been commonly used as a traditional Chinese medicine for its efficacies of hypoglycemic [1], hypolipidemic [2], antihypertensive [3], anti-atherosclerotic [4], anti-inflammatory [5], antioxidant [1,6,7], and antitumor [8]. Phytochemical studies have revealed that mulberry leaf contains various constituents, including flavonoids [9,10], alkaloids [11], polysaccharides [12], amino acids [13], nucleosides, microelements, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…10 Our results show that acidified M. rubra extract exhibited apoptotic features on both A549 and PC-3 cells by reducing mitochondrial membrane potential. Studies have suggested that the anticancer characteristics of phenolic compounds derive from pro-oxidant, rather than antioxidant activities.…”
Section: Discussionmentioning
confidence: 66%
“…21 M. rubra is one of the most important species of the genus Morus, with fruits having substantial levels of phenolics, anthocyanins, carotenoids and ascorbic acid. 3 Many studies have investigated the cytotoxic effects of different berry species, [8][9][10] however to the authors' best knowledge there is no study reporting cytotoxic effect of M. rubra in the literature. It is adviced that in vitro experiments are helpful and advisor for determining first biological effect of a natural or syntetic product.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation